2014
DOI: 10.1128/jvi.00517-14
|View full text |Cite
|
Sign up to set email alerts
|

Productive Replication of Human Papillomavirus 31 Requires DNA Repair Factor Nbs1

Abstract: Activation of the ATM (ataxia telangiectasia-mutated kinase)-dependent DNA damage response (DDR) is necessary for productive replication of human papillomavirus 31 (HPV31). We previously found that DNA repair and homologous recombination (HR) factors localize to sites of HPV replication, suggesting that ATM activity is required to recruit factors to viral genomes that can productively replicate viral DNA in a recombination-dependent manner. The Mre11-Rad50-Nbs1 (MRN) complex is an essential component of the DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
137
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 95 publications
(156 reference statements)
3
137
0
5
Order By: Relevance
“…Importantly, we have demonstrated that Rad51 binds to HPV31 genomes, with binding per genome increasing during productive replication. Knockdown of Rad51 and BRCA1, as well as inhibition of Rad51 activity using a small-molecule inhibitor, is sufficient to block productive replication but not viral genome maintenance, similarly to previously published studies after loss of ATM and MRN activity (4,32). Overall, these studies indicate that HPV may utilize ATM activity to facilitate recombination at viral genomes through Rad51 and BRCA1.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…Importantly, we have demonstrated that Rad51 binds to HPV31 genomes, with binding per genome increasing during productive replication. Knockdown of Rad51 and BRCA1, as well as inhibition of Rad51 activity using a small-molecule inhibitor, is sufficient to block productive replication but not viral genome maintenance, similarly to previously published studies after loss of ATM and MRN activity (4,32). Overall, these studies indicate that HPV may utilize ATM activity to facilitate recombination at viral genomes through Rad51 and BRCA1.…”
supporting
confidence: 67%
“…MRN facilitates the activation of ATM in response to DSBs and also functions downstream of ATM to facilitate HR repair, as mentioned above. We found that disruption of the MRN complex through depletion of Nbs1 abrogates productive replication of HPV31 and blocks the recruitment of Mre11 and Rad50, as well as Rad51, to viral genomes (32). Given the importance of ATM, the MRN complex, Rad51, and BRCA1 to DSB repair through HR, these results suggest that recombination may play a role in the amplification of HPV genomes.…”
mentioning
confidence: 79%
See 3 more Smart Citations